Resistencia química del hormigón. XXVII. Contribución al estudio del sistema: cemento P-550-ARI hidratado-agua desionizada - M. Francisca Bermejo-Muñoz; José Luis Sagrera-Moreno; Demetrio Gaspar-Tébar (Materiales de Construccion, 1987)
In this work, which is the following of others, the performance of a portland cement of a high initial resistance (P-550-ARI) —with a calculated content (Bogue) of 39,2% of C3S, of 25,7% of C2S, of 9,9% of C3A, of 12,0% of C4AF and of 6,9% of CaSO4 — is studied when it is submitted to the action of deionized water running across the beds of granulated cement, made with this hydrated cement cured during 7 or 28 days, determining: a) the evolution of the content on ions Ca (II) and SO4 (II) on the taken diverse fractions of deionized water which have ran across those beds, so as this of the pH and of the conductivity, b) the variation in the amount of these ions that are forming the correspondent compounds, in the hydrated cement from the beds that have been submitted before and after to the action of the deionized water, and c) the structural modification undergone by the crystalline compounds of the hydrated cement from the beds submitted to the action of the deionized water.